Kajian Mutu Kimia, Mikrobiologi dan Organoleptik Limbah Ampas Tahu Segar dari Sentra Produksi Kekalik, Kota Mataram - Kencanadewi, Baiq Citra; Handayani, Baiq Rien; Nazaruddin, Nazaruddin; Bachmida, Elya Antariksana (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2025)
Okara, or tofu dregs, is a by-product of tofu production that still has fairly high nutritional value. This study aims to assess the chemical, microbiological, and organoleptic quality of fresh tofu pulp waste from the Kekalik production center in Mataram City. A stratified random sampling method was employed, with samples collected from six production locations: Kekalik Kijang, Kekalik Timur 1, Kekalik Timur 2, Kekalik Barat, Kekalik Gerisak 1, and Kekalik Gerisak 2. The results revealed significant differences in pH, protein content, and color perception among the okara samples from various locations (p<0.05). However, water activity value, texture perception, and aroma perception did not differ significantly. The okara samples exhibited high water activity, low pH, and low protein content and tested negative for formaldehyde or borax. Microbiologically, okara samples from Kekalik Gerisak 1 and Kekalik Gerisak 2 exhibited the least microbial contamination (5.9×10⁵ CFU/g and 6.6×10⁵ CFU/g, respectively), with minimal coliform presence (<3.0 MPN/g). Organoleptically, panelists tended to prefer brownish-white okara that were slightly mushy and flavorful. Overall, the okara from Kekalik Gerisak 1 was of the highest quality and demonstrated its potential as a safe and valuable food ingredient.